In vivo detection of porcine reproductive and respiratory syndrome virus RNA by in situ hybridization at different times postinfection. - Sur, J H (1996)
We studied the distribution of porcine reproductive and respiratory syndrome virus (PRRSV) RNA in tissues by in situ hybridization at different times postinfection (p.i.). The probe used for in situ hybridization was prepared by reverse transcription of PRRSV RNA, followed by PCR amplification of the cDNA. The sequence amplified corresponded to 433 bp from PRRSV open reading frame 7, which is contained in the nucleocapsid protein gene and which is highly conserved in both European and American strains (H. Mardassi, L. Wilson, S. Mounir, and S. Dea, J. Clin. Microbiol. 32:2197-2203, 1994). An immunohistochemical technique was used to detect PRRSV antigen in tissue from virus-infected animals by using a monoclonal antibody specific for the PRRSV nucleocapsid protein (E.A. Nelson, J. Christopher-Hennings, T. Drew, G. Wensvoort, J.E. Collins, and D.A. Benfield, J. Clin. Microbiol. 31:3184-3189, 1993). The detection of PRRSV RNA was conducted in tissues of 6-week-old pigs that had been infected with one of three different field PRRSV isolates and collected at times ranging from 4 to 42 days p.i. Hybridization signals specific for PRRSV RNA were detected in lung, lymphoid tissues, alveolar macrophages (obtained by lavage at the time of necropsy), Peyer's patches, and kidney. The PRRSV-positive cells in these tissues appeared to be predominantly macrophages. In lung tissue we also obtained evidence suggesting the involvement of type II pneumocytes in the replication of PRRSV. During the acute period of infection there was a close correlation between the detection of RNA and the detection of nucleocapsid protein in individual cells. At later times p.i. (28 and 42 days p.i.), instead, more cells containing only PRRSV RNA than those containing PRRSV RNA and also expressing PRRSV nucleocapsid protein were detected. These results suggest that PRRSV RNA might persist in the tissues of infected animals for a longer time than PRRSV antigen expression.